Molecular identification and functional analysis of HrpZ2, a new member of the harpin superfamily from Pseudomonas syringae, inducing hypersensitive response in tobacco - Lal, Kishori; Joshi, Anurag; Saini, Vartika; Mohammed, Mujahid; Sarma, Pullabhotla V. S. R. N; Dey, Debashish (Frontiers in Plant Science, 2026)
Harpins belong to a group of proteins with distinctive features such as heat stability, glycine richness, and absence of cysteine and are secreted by many Gram-negative phytopathogens via the type III secretion system. Harpins are known to trigger hypersensitive response followed by induction of systemic acquired resistance in non-host plants. However, the molecular mechanism of harpin-induced hypersensitive response remained largely unexplored, mainly because of the lack of structural information. In this study, we report the cloning of a new harpin gene (hrpZ2) from the Pseudomonas syringae strain MTCC-11950, belonging to the harpin superfamily. In silico analysis revealed that approximately 50.29% of the protein consists of α-helices, 48.53% are random coils, and only 1.16% are β-sheets, and nearly half (42%) of the protein consists of intrinsically disordered regions. Based on a prokaryotic predictive model and the presence of a signal peptide on its N-terminus, the subcellular localization of harpin is predicted as extracellular. To date, no experimentally determined crystal structure of any harpin protein is available. Therefore, we built and validated a three-dimensional model (with 99% of residues in allowed/additionally allowed regions and a Z-score of −5.3) of harpin. Phylogenetic analysis and functional domain studies revealed that this new harpin belongs to the harpin superfamily. Infiltration of harpin in tobacco leaves resulted in a hypersensitive response, which was associated with oxidative burst, callose deposition, localized cell death, and increased activity of defense-related enzymes such as phenylalanine ammonia-lyase and polyphenol oxidase. Furthermore, infiltration of harpin in non-host plants from different angiosperm families induced a hypersensitive response, indicating broad-spectrum agricultural applicability of this new harpin protein. This study elucidates the molecular and functional properties of the new harpin protein and its ability to induce hypersensitive response across a broad range of non-host plants.